Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1155/2023/7510452
|View full text |Cite
|
Sign up to set email alerts
|

The Use of D-Optimal Mixture Design in Optimizing Formulation of a Nutraceutical Hard Candy

Abstract: The aim of this study was to optimize the formulation of hard candy with antiviral herbal extracts and flowered with Citrus limon peel essential oils. To substitute water fraction, the D-optimal mixture design was used. The optimized mixture fractions of the best hard candy formulation contain Curcuma longa extract (10%), Artemisia herba-alba Asso extract (3.33%), Glycyrrhiza glabra extract (1.66%), and Zingiber officinale extract (1.66%) and flowered by 20 μL/100 gram of Citrus limon essential oils. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(58 reference statements)
0
1
0
2
Order By: Relevance
“…Se elaboran a partir de un jarabe de sacarosa sometido a altas temperaturas, con la adición de agentes como glucosa y fructosa para evitar el crecimiento de los cristales de sacarosa (Souiy et al, 2023). Esta categoría incluye caramelos macizos, masticables, frágiles y gomosos.…”
Section: Productos De Confitería Y Su Disponibilidad En El Mercadounclassified
See 1 more Smart Citation
“…Se elaboran a partir de un jarabe de sacarosa sometido a altas temperaturas, con la adición de agentes como glucosa y fructosa para evitar el crecimiento de los cristales de sacarosa (Souiy et al, 2023). Esta categoría incluye caramelos macizos, masticables, frágiles y gomosos.…”
Section: Productos De Confitería Y Su Disponibilidad En El Mercadounclassified
“…Durante el proceso de enfriamiento, se incorporan colorantes y saborizantes a la mezcla, la cual se amasa para finalmente obtener la forma deseada (Hinkova et al, 2014;Souiy et al, 2023).…”
Section: Productos De Confitería Y Su Disponibilidad En El Mercadounclassified
“…The alcohol draws out the fragrance on its own, without taking on the fats. This extraction technique is virtually dying out due to its high cost, and the extracted oils have no applications in the food industry [14,22,23].…”
Section: Enfleuragementioning
confidence: 99%
“…Some recent studies documented the formulation of candies with substitutes of the commonly used ingredients to circumvent the deleterious effects of candy consumption. Few researchers have successfully incorporated spices such as a mixture of turmeric, ginger, liquorice, white wormwood, and citrus lemon extracts (11) to develop antioxidant-rich hard candies. Several studies have reported the formulation of fruit candies utilizing various fresh fruits, including unripe mango (12).…”
Section: Introductionmentioning
confidence: 99%